In the details: the micro-ethics of negotiations and in-situ judgements in participatory design with marginalised children. Issue 1 (2nd January 2020) - Spiel, Katta; Brulé, Emeline; Frauenberger, Christopher; Bailley, Gilles; Fitzpatrick, Geraldine
ABSTRACT: Engaging marginalised children, such as disabled children, in Participatory Design (PD) entails particular challenges. The processes can effect social changes by decidedly attending to their lived experience as expertise. However, involving marginalised children in research also requires maintaining a delicate balance between ensuring their right to participation as well as their protection from harm. The resulting tensions are politically charged, affected by myriads of power differences and create moral dilemmas. We present seven case studies, drawing from two participatory design research projects. They illustrate the in-situ judgements taken to address specific dilemmas and provide nuanced insights into the trade-offs required by child-led participatory design processes. Subsequently, we identify three challenges: positioning our work to the children's carers' values, protecting ourselves, and enabling the (relative) risk-taking associated with participation for children. We call for this micro-ethical approach to be used when reporting research ethics in practice, and as a guidance for the training of researchers and practitioners.